2013
DOI: 10.1002/eji.201343790
|View full text |Cite
|
Sign up to set email alerts
|

Human dendritic cells — stars in the skin

Abstract: "A properly functioning adaptive immune system signifies the best features of life. It is diverse beyond compare, tolerant without fail, and capable of behaving appropriately with a myriad of infections and other challenges. Dendritic cells (DCs) are required to explain how this remarkable system is energized and directed." This is a quote by one of the greatest immunologists our community has ever known, and the father of dendritic cells, Ralph Steinman. Steinman's discovery of DCs in 1973 and his subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 106 publications
0
22
0
Order By: Relevance
“…Human skin is known to contain four distinct mDC subsets. Three of these, marked as CD1a + LCs are found in the epidermis (3,23). To define unique surface markers and to fully characterize expression patterns of each epidermal and dermal subset, we performed a flow cytometry analysis of 332 different surface proteins.…”
Section: Cd5 Marks a Subset Of Epidermal Lcs And Dermal Cd1amentioning
confidence: 99%
“…Human skin is known to contain four distinct mDC subsets. Three of these, marked as CD1a + LCs are found in the epidermis (3,23). To define unique surface markers and to fully characterize expression patterns of each epidermal and dermal subset, we performed a flow cytometry analysis of 332 different surface proteins.…”
Section: Cd5 Marks a Subset Of Epidermal Lcs And Dermal Cd1amentioning
confidence: 99%
“…LCs (Langerin+, CD1a+) constituting subsets of DCs populating epidermis have been explored extensively along with interstitial DCs, namely, resident dermal myeloid DCs (CD11c+, CD1c+), plasmacytoid blood DCs (BDCA-2+, CD123+), and a dermal population of CD14+ CD11c+ DCs found in normal skin, by other authors, who suggested that inflammatory skin diseases are characterized by a particular DC profile [70,71]. Over time, the spectra of effects of LCs on peripheral T cells, activation of skin resident memory T lymphocytes, a defense function against pathogens and tissue repair were explored [72,73]. In our study, immunohistochemical results of S100 staining observed in the case of classic LPP and LP, both intraepithelial LCs and dermal DCs, are consistent with the results of Santoro et al [49].…”
Section: Discussionmentioning
confidence: 99%
“…DC can be found in lymphoid and nonlymphoid tissues, including blood, lymph nodes, tonsils, spleen, skin, liver, kidneys, lungs and gut [12,14,49,57,[60][61][62][63][64][65]. Transcriptome analysis demonstrates a clear relationship between CD1c ?…”
Section: Human Dendritic Cellsmentioning
confidence: 99%